Treatment of rubber effluent from rubber processing plant with fungi - IGIEBOR, Francis Aibuedefe; OKOYE, Pascal Chukwuebuka; EVBUOMWAN, Oghoreye Nosa (Studia Universitatis Babeș-Bolyai Biologia, 2018)
Rubber processing industry produces materials used for the manufacturing of rubber industrial products. Large volume of water is consumed and produces a huge amount of effluent which is later discharged into the waterways, thereby causing pollution that affects human health. The effluent was collected from discharge points of a rubber factory. Microbial analyses were carried out before and after pollution. During the incubation, microbial growth in culture tubes was determined using UV-Spectrophotometer by measuring absorbance at wavelength 600nm at 24 hours interval. Four fungi were isolated and identified from rubber effluents which include Mucor mucedo and Aspergillus niger, Aspergillus flavus and Penicillium notatum. Individually, the selected fungi isolates were tested for its efficiency on the bioremediation of rubber processing effluent. The physicochemical properties reduction of the effluent such as BOD, COD, TS, TSS, TDS, phosphate and ammonia were observed after incubating for 7 days. Based on the data obtained in this study, it can be concluded that Mucor mucedo and Aspergillus niger can be used for bioremediation of rubber processing industry effluent with high efficiency.